"Stiction Syndrome": Non-Operative Management of Patients with Difficult AMS 700 Series Inflation. Issue 9 (1st September 2017) - Kavoussi, Nicholas L.; Viers, Boyd R.; VanDyke, Maia E.; Pagliara, Travis J.; Morey, Allen F.
Abstract: Introduction: Static friction (stiction) is a mechanical phenomenon in which a state of increased resistance exists across a control valve mechanism. Aim: To present a strategy for non-operative management of inflatable penile prosthesis (IPP) cases with pump malfunction from pump valve stiction. Methods: All patients had American Medical Systems (AMS; Minnetonka, MN, USA) 700 series Momentary Squeeze IPPs with transient pump malfunction owing to pump valve stiction after extended periods of device inactivity. Main Outcome Measures: Our evolving non-operative management experience with the "forced deflation" maneuver is described. This technique has successfully prevented the need for surgical pump replacement. Of patients with IPP who were instructed to inflate and deflate daily to prevent stiction recurrence, none have re-presented with difficult inflation. Results: Of 306 patients receiving the AMS 700 series IPP at our institution from 2007 through 2015, 6 (1.9%) presented with difficulty activating the Momentary Squeeze pump (from 2011 through 2015). Four additional patients were referred from outside institutions with the same complaint. All patients (10 of 10, 100%) presented after a prolonged period of inactivity (minimum = 6 weeks) during which the IPP was not cycled and remained stagnant. Although the initial four patients (40%) underwent surgical exploration with pump mobilization and replacement, the six most recent patients (60%) were successfully instructed in the forced deflation maneuver in the office, which enabled the device to cycle normally thereafter. Conclusion: Device inactivity, for as little as 6 weeks, can predispose to Momentary Squeeze pump valve malfunction; and a regimen of daily IPP cycling could prevent stiction-related malfunction. Our findings should encourage practitioners to attempt conservative management of patients with "stiction syndrome" whenever possible, thereby avoiding unnecessary surgery.